Effect of dietary fat source on the composition of the cecal microbiome in maturing broiler chicken - Jadhav, Vidya V.; Fasina, Yewande; Omaliko, Paul C.; Han, Jian; Harrison, Scott H. (Frontiers in Microbiology, 2024)
Diet has been found to significantly influence gut microbiota throughout various life stages, and gut microbiota have been increasingly shown to influence host physiology, health, and behavior. This study uses 16S rRNA sequencing to examine the effects of six different fat-supplemented diets (canola oil, coconut oil, fish oil, flaxseed oil, lard, and olive oil) on broiler chicken cecal microbial composition and predicted function in comparison with a common and inexpensive fat source (poultry fat). Groups of broilers were fed each of these diets and then evaluated on day 41 and day 55 of age. For both 41- and 55-day samples, Firmicutes and Bacteroidetes phyla were the dominant bacteria in the ceca accounting for 99% of the microbial community. Across the 41- and 55-day samples, treatment time was associated with a stronger and more significant microbiota shift (p < 0.001) than differences in dietary treatment alone (p = 0.117), but dietary treatment combined with treatment time is a significant factor as well (p = 0.047). Sparse partial least squares discriminant analysis was used to explore the more discriminating taxa for each treatment group. For identified species, butyrate production appears to be affected in a diet-specific manner, with many butyrate-producing species being evident for the fish-based diet at day 41 and a few of these species for the flaxseed-based diet at day 55. Predicted functions, as conducted with PICRUSt2, were significant for comparisons between the control and the flaxseed-based dietary treatment group at day 55, with indications of host health benefit for the flaxseed-based diet. Predicted functions found to be significant were for enzymes and pathways such as propionate CoA ligase, aminobutyraldehyde dehydrogenase, vitamin B12-transporting ATPase, thiamine kinase, acetylneuraminate epimerase, and L-tryptophan biosynthesis. This study provides insight surrounding specific dietary fat-based treatments to be investigated further and highlights the importance of polyunsaturated fat sources in poultry feed that may offer a favorable cecal microbial modulation compared to saturated fat sources.